2020
DOI: 10.5663/aps.v8i2.29349
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Perceptions of Bullying at School among First Nations Youth Living Off Reserve

Abstract: This study described perceptions of bullying as a school characteristic and associations with school, academic, and health characteristics among a representative sample of First Nations high school students living off reserve in Canada using data from the 2012 Aboriginal Peoples Survey. Almost 4 in 10 of First Nations youth living off reserve perceived bullying as a problem at their schools. A perceived climate of bullying co-occurred with other negative school climate characteristics such as racism, violence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Four studies (CAN = 1; NA = 1; and AUS = 2) examined relations between racism and bullying (Arim et al., 2020; Melander et al., 2013; Priest et al., 2019; Priest et al., 2016). Arim et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies (CAN = 1; NA = 1; and AUS = 2) examined relations between racism and bullying (Arim et al., 2020; Melander et al., 2013; Priest et al., 2019; Priest et al., 2016). Arim et al.…”
Section: Resultsmentioning
confidence: 99%
“…Arim et al. (2020) found that First Nations Canadian youth who perceived high levels of bullying at school were likely to report high levels of perceived discrimination; bullying was then linked to psychological distress and lifetime suicidal ideation. Melander et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations